Design of a simple detection cell with extended optical path length for capillary electrophoresis: Application to multiresidue pesticide analysis - Galhiane, Mario Sergio [UNESP]; Rissato, SR; Apon, B. M. (Taylor & Francis Inc, 2005)
Absorbance detection in capillary electrophoresis (CE), offers an excellent mass sensitivity, but poor concentration detection limits owing to very small injection volumes (normally I to 10 nL). This aspect can be a limiting factor in the applicability of CE/UV to detect species at trace levels, particularly pesticide residues. In the present work, the optical path length of an on-column detection cell was increased through a proper connection of the column (75 mu m i.d.) to a capillary detection cell of 180 mu m optical path length in order to improve detectability. It is shown that the cell with an extended optical path length results in a significant gain in terms of signal to noise ratio. The effect of the increase in the optical path length has been evaluated for six pesticides, namely, carbendazim, thiabendazole, imazalil, procymidone triadimefon, and prochloraz. The resulting optical enhancement of the detection cell provided detection limits of ca. 0.3 mu g/mL for the studied compounds, thus enabling the residue analysis by CE/UV.
Keywords: pesticide residue analysis; capillary electrophoresis (CE); detection cell; CE/UV